Association between discharge heart rate and left ventricular adverse remodelling in ST segment elevation myocardial infarction patients treated with primary percutaneous coronary intervention. Issue 8 (6th March 2013) - Joyce, Emer; Hoogslag, Georgette E; Leong, Darryl P; Fox, Kim; Schalij, Martin J; Marsan, Nina Ajmone; Bax, Jeroen J; Delgado, Victoria
Abstract : Objective: Left ventricular (LV) adverse remodelling is an important determinant of mortality after ST segment elevation myocardial infarction (STEMI). Recently, discharge heart rate (DHR) has been associated with long-term outcomes after STEMI. Whether DHR is related to the development of LV remodelling after STEMI remains unknown. The present study evaluated the association between DHR after STEMI and the occurrence of LV remodelling at 6 months. Design, setting, patients and interventions: In 964 STEMI patients (60±11 years, 77% male) treated with primary percutaneous coronary intervention, DHR was derived from predischarge 12-lead electrocardiograph. LV volumes were measured with two-dimensional transthoracic echocardiography at baseline and 6-month follow-up. Variables independently associated with the occurrence of LV remodelling were investigated. Main outcome measures: LV remodelling, defined as ≥20% increase in LV end-diastolic volume at 6 months follow-up. Results: LV remodelling occurred in 30.7% of patients. Compared with patients without remodelling, these patients had higher DHR (72±11 bpm vs 68±12 bpm, p<0.001), higher levels of peak troponin T (5.6 (2.7, 11) ug/L vs 3.7 (1.6, 7.4) ug/L, p<0.001) and creatine kinase (2083 (960, 4045) U/L vs 1469 (669, 2750) U/L, p<0.001), lower LV ejection fraction (45±10 vs 48±9%, p<0.001) and more frequently displayed left anterior descending artery as culprit (52% vs 44%, p=0.02). Median DHR was 69 bpm. DHR >69 bpm (OR 1.5, 95% CI 1.10 to 2.04, p=0.01) and higher peak troponin T (OR 1.06, 95% CI 1.03 to 1.09, p<0.001) were independently associated with LV remodelling at follow-up. Conclusions: DHR is independently associated with LV remodelling after STEMI, underlining the importance of heart rate as an early risk marker in this contemporary population.